Assessing intra-seasonal land surface change and long term trends in the succulent Karoo biome using coarse resolution satellite and interpolated rainfall surfaces - Roberts, Jonathan Wesley (Department of Environmental and Geographical Science, 2014)
The Succulent Karoo is a biodiversity hot spot situated along the west coast of southern Africa. While it is predominantly recognized as a west coast vegetation type its borders stretch as far east as Steytlerville in the Little Karoo. The area contains the largest number of endemic succulent species in the world and harbors nearly 10 percent of the of the total number of succulent species worldwide. Furthermore, spring mass-flowering events draw thousands of tourists to the region, providing welcome input to the local economies. The floral diversity is however, under threat from various environmental forces. These forces include inappropriate land use practices resulting in Land Degradation and the ever-present threat of Climate Change.